Ethos and vision realization in sponsored academy schools. (January 2015) - Gibson, Mark T
This article investigates the realization of ethos and vision in the early stages of sponsored academy schools in England. It is a qualitative nested case study of ten academies. Nineteen key actors were interviewed, including principals and sponsor representatives. The nests were organized by sponsor type. Key themes are discussed within the context of the literature. There were common themes across all of the academies and some that were exclusive to individual cases. The conclusions drawn show that the leaders of these schools were initiating several actions simultaneously in order to develop their academies' ethos and vision. The ethos and vision realization in sponsored academy schools is more complex than other examples in the literature owing to a greater number of actors and the urgency for change. In particular, the role of the sponsor is greater than much of the literature suggests.